Pengaruh Dana Pihak Ketiga, Kredit yang Disalurkan dan Kredit Non Lancar Terhadap Laba(The Impact Of Third parties funds, DistributedLoans On Profitabilites) (Studi Kasus Pada Bank Nusantara Parahyangan Cabang Sudirman) - Dwi Rianawati; Nur Imam Taufik (Universitas Kristen Maranatha, 2018)
Bank as a financial institution is a business-oriented entity that is aiming to make profit/earnings through ethical ways including through fulfillment of customer needs and satisfaction. As commodities are processed and sold by the bank is fund that will also be the object of its business. Bank is a business entity which functions to collect funds from the public in the form of deposits, and also serves to distribute in the form of credit and other forms to the public or the debtor. The distribution is likely to impact the risk be less smooth return of the loan amount or also known as Non-Performing Loans (NPL), which will affect the company's financial banking. Non-performing loans are credit distributed loans, but the loans are substandard, doubtful and loss. The amount of data that is used as much as 42 months, they are the data of Third Party Fund, Distributed Loans andÂ Non Performing LoansÂ of Bank Nusantara Parahyangan, and also its profit from the period of January 2013- June 2016. The data were analyzed in this study using a linear regression model, and the results are Third Party Fund has significant effect on profit growth level at the Bank Nusantara Parahyangan Sudirman branch; The amount of Distributed Loans does not have significant effect on profit growth level at Bank Nusantara Parahyangan Sudirman branch; The amount of Non Performing Loans does not have significant effect on profit growth level at Bank Nusantara Parahyangan Sudirman branch; Research shows the variable of the Amount of Third Party Funds, Distributed Loans, and Non Performing Loans simultaneously have a significant effect on profit grow level at Bank Nusantara Parahyangan Sudirman branch.Â Keywords: Impact of TPF, DL, NPL, Profit